Scientific reasoning and objectivity in realia-based elementary science learning - Lilik Bangun Yunianto; Kartika Chrysti Suryandari; Septi Triyani (Journal of Professional Teacher Education, 2026)
The findings suggest that integrating claim-evidence-reasoning scaffolds into realia-based science instruction at the associating stage can strengthen students’ objectivity and reasoning skills while fostering multiple scientific attitudes in the Indonesian elementary science curriculum. This study aims to (1) describe the preparation and implementation of realia media through the scientific method, (2) analyze fifth-grade students’ scientific attitude profiles across five dimensions (curiosity, responsibility, independence, honesty, and objectivity), and (3) identify supporting and inhibiting factors. A qualitative-dominant mixed-methods case study was conducted at SDN 1 Wonogiri, a public elementary school in Wonogiri, Central Java, Indonesia. The participants included three classroom teachers and 297 fifth-grade students. Qualitative data from classroom observation and in-depth interviews were primary, complemented by descriptive data from a validated student response questionnaire, and were analyzed using the interactive model of Miles and Huberman. Four dimensions developed consistently, with positive responses from 88 to 100 percent, whereas objectivity remained the most vulnerable dimension, particularly at the reasoning stage. Supporting factors included the availability of authentic objects and material relevance to daily experience; inhibiting factors included limited instructional time and students’ uneven reasoning capacity. The study provides a multidimensional profile of five attitudes, identifies reasoning capacity as strongly associated with objectivity, and reports a discrepancy between self-reported and observed objectivity. The findings imply that realia-based science instruction should incorporate claim-evidence-reasoning scaffolds at the associating stage to strengthen students’ objectivity and reasoning skills while guiding teachers in designing learning activities that simultaneously foster multiple scientific attitudes within the Indonesian elementary science curriculum.